2018
DOI: 10.1002/vnl.21676
|View full text |Cite
|
Sign up to set email alerts
|

Gelation of poly(vinyl chloride) inside a single screw extruder and its effect on product properties

Abstract: Two resin formulations were extruded through a single screw extruder, equipped with a single flighted screw, rotating at 10 rpm, at different barrel temperature settings, which resulted in different melt temperatures measured in the adapter zone. The extrudates were subsequently subjected to assessments of the gelation level by three different methods: differential scanning calorimetry (DSC), capillary rheometry (CR), and solvent absorption (SA). The pros and cons of these methods are discussed. It appears tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…In the case of the degree of gelation, it is observed that the pipe samples exhibit very different values. U‐PVC‐1 is in the lower limit established in the literature ( DG ~60%), [ 8,10 ] and M‐PVC‐2 appears to have been gelled in excess ( DG >90%).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the case of the degree of gelation, it is observed that the pipe samples exhibit very different values. U‐PVC‐1 is in the lower limit established in the literature ( DG ~60%), [ 8,10 ] and M‐PVC‐2 appears to have been gelled in excess ( DG >90%).…”
Section: Resultsmentioning
confidence: 99%
“…[ 5 ] It is widely accepted that an adequate gelation level of a U‐PVC composition is between 60 and 90%. [ 8,10 ] In this situation, the primary particles exhibit a high degree of cohesion with the presence of extremely strong bonding forces, with the persistence of small structural voids that act as stress relievers. [ 11 ]…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The stabilizer package also includes lubricants. These PVC formulations are commercial grades used for cable duct (resin A) and window profile (resin B) extrusion applications [ 18 ]. The formulations were mixed in a Zeppelin Reimelt Henschel FML10/KM 23 hot-cold mixer (Kassel, Germany).…”
Section: Equipment and Rheological Characterizationmentioning
confidence: 99%